Prediction of higher visual function in macular degeneration with multifocal electroretinogram and multifocal visual evoked potential. (26th August 2014) - Herbik, Anne; Geringswald, Franziska; Thieme, Hagen; Pollmann, Stefan; Hoffmann, Michael B.
Abstract Objective Visual search can be guided by past experience of regularities in our visual environment. This search guidance by contextual memory cues is impaired by foveal vision loss. Here we compared retinal and cortical visually evoked responses in their predictive value for contextual cueing impairment and visual acuity. Methods Multifocal electroretinograms to flash stimulation (mfERGs; 103 locations; 55.8° diameter) and visual evoked potentials to pattern‐reversal stimulation (mfVEPs; 60 locations; 48.6° diameter) were recorded monocularly in participants with age‐related macular degeneration (n = 14 and 16, respectively). Response magnitudes were calculated as the respective signal‐to‐noise ratios for each eccentricity. Visual acuities (logMAR, range: 0.0–1.2) and contextual cueing effects on visual search (reaction time gain, range: −0.14–0.15) were correlated with the signal‐to‐noise ratios. A step‐wise regression analysis was applied separately to the mfERG‐ and mfVEP‐dataset to determine the eccentricity range and the processing stage that is critical for these visual functions. Results Central mfERGs (1.0–3.2°) were the sole predictor of contextual cueing of visual search (p = 0.006), but they were not significant predictors of visual acuity. In contrast, central mfVEPs (1.3–3.2°) were the sole predictor of visual acuity (p < 0.001), but they were not significant predictors of contextual cueing. Conclusions Contextual cueing is more dependent on parafoveal mfERG magnitude while visual acuity is more dependent on parafoveal mfVEP magnitude. The relation of contextual cueing to parafoveal mfERG magnitudes indicates the predictive value of retinal bipolar cell activity for this advanced level of visual function.